Malay-English language alternation in two Brunei Darussalam on-line discussion forums - McLellan, James A. H. (Curtin University, 2005)
This is a study of language choice and language alternation patterns in a corpus of messages posted on two Brunei Darussalam on-line discussion forums. It aims to break new ground by investigating Malay-English language alternation in the context of computer-mediated communication (CMC), in contrast to previous research which has mostly studied alternation or code-switching in informal conversations. The corpus of texts consists of 21 1 messages posted on the 'Bruclass' and 'Brudirect' forums. These were analysed in terms of their grammatical and discoursal features to determine what role is played by each of the contributing languages. Chapter 1 outlines the major research questions: how much alternation is there between Malay and English, how is this alternation achieved, and why do the bilingual text producers make these language choices when posting their messages in the on-line forums? This chapter also includes outline description of the sociolinguistic context of Brunei Darussalam in terms of its population, history, system of education, and discussion of the varieties of Malay and of English used by Bruneians. In Chapter 2 relevant literature on language alternation is reviewed, with a gradual narrowing of the focus: from theories of code-switching and language alternation to studies dealing specifically with Malay-English code-switching in Malaysia and in Brunei Darussalam. Studies on language use and alternation in the CMC domain are also reviewed. Chapter 3 discusses the combination of quantitative and qualitative methods, and the rationale for these. Findings from the grammatical and discoursal analyses are reported and discussed in Chapter 4. Whilst monolingual English messages are the most frequent, almost half of the corpus texts are found to include a measure of Malay-English alternation.Many of these display an asymmetric alternation pattern, in which one language supplies the grammar and the other the lexis, but there are also examples of equal alternation, where Malay and English both contribute to the grammar and to the lexis. The reasons for these choices are investigated through a questionnaire survey, which includes a text ranking task, and through other published texts in which Bruneians discuss their use of language. Chapter 5 discusses these findings, and the concluding Chapter 6 considers connections between the analysis of the texts and the questionnaire survey, especially the preference for monolingual English. Chapter 6 also includes discussion of questions of identity as reflected in the language choices and of language use in the CMC domain.